The Influence of Understanding UNPAB Students and Learning Motivation on the Use of Computer-Based Information Systems - Tampubolon, Merna Gletesya; Sirait, Netty Julianti; Aurora, Titania; Wan Fachruddin (Journal of Advances in Accounting, Economics, and Management, 2025)
This study aims to analyze the influence of students' understanding and learning motivation at Universitas Pembangunan Panca Budi (UNPAB) on the utilization of computer-based information systems. A quantitative descriptive research method was employed, with data collected through questionnaires from 31 respondents selected using the Slovin formula. Data analysis included normality tests, linearity tests, multiple linear regression, t-tests, F-tests, and determination coefficients. The findings revealed that students' understanding significantly and positively affects the use of computer-based information systems (effective contribution coefficient: 61.1%). Learning motivation also has a significant and positive influence (effective contribution: 16.1%). Collectively, these two variables contribute 77.2% to the utilization of computer-based information systems. This study emphasizes the importance of enhancing students' understanding and learning motivation to optimize the use of information technology in the learning process. Recommendations include technology training, integrating digital literacy into the curriculum, and creating a supportive learning  environment.